2015
DOI: 10.3892/mmr.2015.4159
|View full text |Cite
|
Sign up to set email alerts
|

Activated farnesoid X receptor attenuates apoptosis and liver injury in autoimmune hepatitis

Abstract: Autoimmune hepatitis (AIH) is a chronic inflammatory liver disease associated with interface hepatitis, the presence of autoantibodies, regulatory T-cell dysfunction and raised plasma liver enzyme levels. The present study assessed the hepatoprotective and antiapoptotic role of farnesoid X receptor (FXR) in AIH. A mouse model of AIH was induced by treatment with concanavalin A (ConA). The FXR agonist, chenodeoxycholic acid (CDCA), was administered to mice exhibiting ConA-induced liver injury and a normal contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Previous studies showed that bile acids, SCFAs, and glutathione were involved in hepatocyte apoptosis. 34 , 39 , 40 The present study performed a metabonomic analysis of SCFAs and bile acids in the livers of Van- and Gen-treated mice (Supplementary Figures S7, S8). The levels of some SCFAs and bile acids in the livers of the Gen-treated mice were significantly higher than the Van-treated mice (Supplementary Figures S7c and S8).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that bile acids, SCFAs, and glutathione were involved in hepatocyte apoptosis. 34 , 39 , 40 The present study performed a metabonomic analysis of SCFAs and bile acids in the livers of Van- and Gen-treated mice (Supplementary Figures S7, S8). The levels of some SCFAs and bile acids in the livers of the Gen-treated mice were significantly higher than the Van-treated mice (Supplementary Figures S7c and S8).…”
Section: Resultsmentioning
confidence: 99%
“…The anti-apoptosis effect of CDCA has been well established by previous studies. For instance, Lian and coworkers demonstrated that CDCA, as a FXR agonist, exerts an anti-apoptotic role in a concanavalin A induced autoimmune hepatitis mouse model via downregulating Fas/Fas ligand, TRAIL, and caspase-3 [29]. Similarly, Hirano and coworkers showed that CDCA inhibited apoptosis through inducing cIAP-1 (cellular inhibitor of apoptosis protein-1) expression in hepatocytes [30].…”
Section: Discussionmentioning
confidence: 99%
“…Both natural ligand CDCA and synthetic agonist GW4064 raised the expression of the suppressor of cytokine signaling 3, a negative regulator of cytokine-STAT3 signaling, contributing to the protection of hepatocellular inflammation [ 77 ]. In addition, the FXR activation also lessened apoptosis and liver injury in concanavalin A-induced autoimmune hepatitis in mice [ 78 ]. A recent study showed that FXR activation by OCA treatment ameliorated the HFD-induced hepatic inflammation through the reprogramming of arachidonate metabolism, by inducing a CYP450 epoxygenase expression [ 79 ].…”
Section: Biological Roles Of Fxr In Various Organs and The Inter-omentioning
confidence: 99%